2021
DOI: 10.3389/fcell.2021.703670
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of Irisin in Attenuating Pathological Features of Osteoarthritis

Abstract: To investigate the effects and mechanisms of irisin, a newly discovered myokine, in cartilage development, osteoarthritis (OA) pathophysiology and its therapeutic potential for treating OA we applied the following five strategical analyses using (1) murine joint tissues at different developmental stages; (2) human normal and OA pathological tissue samples; (3) experimental OA mouse model; (4) irisin gene knockout (KO) and knock in (KI) mouse lines and their cartilage cells; (5) in vitro mechanistic experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Our results also confirmed those of a previous study by Vadala et al (2020) , who suggested that irisin could reduce the expression of type X collagen, as well as IL-1, IL-6, MMP-1, MMP-13, and inducible nitric oxide synthase (iNOS) through inactivating the p38 MAPK, Akt, JNK, and NFκB signaling pathways. Li et al (2021) reported that irisin is involved in chondrogenesis and the pathogenesis of OA, and abnormal changes in the expression of irisin in OA cartilage suggest that irisin is a promising therapeutic target. To further validate our findings, we established an exercise protocol to measure exercise-induced irisin levels and investigate the role of irisin in exercise therapy for treating OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also confirmed those of a previous study by Vadala et al (2020) , who suggested that irisin could reduce the expression of type X collagen, as well as IL-1, IL-6, MMP-1, MMP-13, and inducible nitric oxide synthase (iNOS) through inactivating the p38 MAPK, Akt, JNK, and NFκB signaling pathways. Li et al (2021) reported that irisin is involved in chondrogenesis and the pathogenesis of OA, and abnormal changes in the expression of irisin in OA cartilage suggest that irisin is a promising therapeutic target. To further validate our findings, we established an exercise protocol to measure exercise-induced irisin levels and investigate the role of irisin in exercise therapy for treating OA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exercise could increase the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) and its coactivator-1-α (PGC-1α) in muscles, thus facilitating the downstream generation of FNDC5 and its proteolytic cleavage to form irisin ( Hecksteden et al, 2013 ; Aydin, 2014 ; Norheim et al, 2014 ). Although irisin has been reported to exert anti-osteoarthritic effects in chondrocytes ( Li et al, 2021 ; Vadala et al, 2020 ), its role in the exercise therapy of osteoarthritis (OA) remains unknown. As an exercise-induced myokine, we hypothesized that irisin could be a key exercise factor in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Irisin treatment was discovered to improve bone metabolism and thus prevented the osteoporosis [ 22 , 41 ]. Regarding the regulation of cartilage degenerative diseases, irisin was found to display chondroprotective effects on the development of osteoarthritis and played a powerful role in the regulation of ECM metabolic disorder [ 25 , 26 ]. Nevertheless, the effects of irisin on NPCs are not well known yet.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, accumulating studies have shown that irisin plays an essential role against the progression of skeletal degenerative diseases such as osteoporosis and osteoarthritis [21][22][23][24]. Besides, it has been reported that irisin is a powerful regulator of the metabolism of ECM, including upregulating the levels of COL2A1 and ACAN and downregulating the productions of matrixdegrading enzymes in chondrocytes [25,26]. As yet, however, much remains unknown about irisin's effects on the regulation of ECM metabolism in NPCs in the progression of IDD.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, irisin treatment prevented loss of bone mass and improved bone metabolism [ 16 , 17 ], while in vitro, irisin has been found to enhance the osteoblastogenetic process of MSCs, respectively [ 18 , 19 ]. In addition, Li et al [ 20 ] discovered that irisin was involved in the development of articular cartilage, and Wang et al [ 21 ] found that irisin displayed chondroprotective effects on the development of osteoarthritis. Despite its considerable roles in the regulation of skeletal metabolism, it remains elusive whether irisin regulated the chondrogenic differentiation of hMSCs.…”
Section: Introductionmentioning
confidence: 99%